An electrocorticographic electrode array for simultaneous recording from medial, lateral, and intrasulcal surface of the cortex in macaque monkeys - Fukushima, Makoto (2014)
BACKGROUND: Electrocorticography (ECoG) permits recording electrical field potentials with high spatiotemporal resolution over a large part of the cerebral cortex. Application of chronically implanted ECoG arrays in animal models provides an opportunity to investigate global spatiotemporal neural patterns and functional connectivity systematically under various experimental conditions. Although ECoG is conventionally used to cover the gyral cortical surface, recent studies have shown the feasibility of intrasulcal ECoG recordings in macaque monkeys. NEW METHOD: Here we developed a new ECoG array to record neural activity simultaneously from much of the medial and lateral cortical surface of a single hemisphere, together with the supratemporal plane (STP) of the lateral sulcus in macaque monkeys. The ECoG array consisted of 256 electrodes for bipolar recording at 128 sites. RESULTS: We successfully implanted the ECoG array in the left hemisphere of three rhesus monkeys. The electrodes in the auditory and visual cortex detected robust event related potentials to auditory and visual stimuli, respectively. Bipolar recording from adjacent electrode pairs effectively eliminated chewing artifacts evident in monopolar recording, demonstrating the advantage of using the ECoG array under conditions that generate significant movement artifacts. COMPARISON WITH EXISTING METHODS: Compared with bipolar ECoG arrays previously developed for macaque monkeys, this array significantly expands the number of cortical target areas in gyral and intralsulcal cortex. CONCLUSIONS: This new ECoG array provides an opportunity to investigate global network interactions among gyral and intrasulcal cortical areas.